2022
DOI: 10.20892/j.issn.2095-3941.2020.0727
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood indices to predict PFS/OS with anlotinib as a subsequent treatment in advanced small-cell lung cancer

Abstract: Objective: In the phase II ALTER-1202 (NCT03059797) trial, anlotinib significantly improved progression-free survival (PFS) and overall survival (OS) in patients with advanced small-cell lung cancer (SCLC) who underwent at least 2 previous chemotherapy cycles, when compared with a placebo group. To identify potential factors for predicting efficacy and prognosis with anlotinib treatment, we analyzed hematological indices at baseline and adverse events (AEs) over the course of anlotinib treatment. Methods: Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Our study found that post‐NLR elevation was an independent prognostic factor of PFS but not for OS, as Cuicui Zhang et al described. 10 Although we found similar results in this study but did not share the same cut‐off value, which is 240.56 in SCLC and 205.63 in NSCLC, the conclusion from our previous study about NSCLC patients receiving anlotinib indicated that high pre‐PLR was related to poor outcome. 7 This phenomenon revealed the existence of different tumors with different cutoff values and the possibility of the difference being caused by insufficient sample capacity.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our study found that post‐NLR elevation was an independent prognostic factor of PFS but not for OS, as Cuicui Zhang et al described. 10 Although we found similar results in this study but did not share the same cut‐off value, which is 240.56 in SCLC and 205.63 in NSCLC, the conclusion from our previous study about NSCLC patients receiving anlotinib indicated that high pre‐PLR was related to poor outcome. 7 This phenomenon revealed the existence of different tumors with different cutoff values and the possibility of the difference being caused by insufficient sample capacity.…”
Section: Discussionsupporting
confidence: 59%
“…It could be due to the various follow-up treatments or other unknown factors. Our study found that post-NLR elevation was an independent prognostic factor of PFS but not for OS, as Cuicui Zhang et al described 10. Although we found similar results in this study but did not share thesame cut-off value, which is 240.56 in SCLC and 205.63 in NSCLC, the conclusion from our previous study about NSCLC patients receiving anlotinib indicated that high pre-PLR was related to poor outcome.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…In addition, anlotinib is an oral multi-target tyrosine kinase inhibitor that selectively inhibits vascular endothelial growth factor receptor, fibroblast growth factor receptor, platelet-derived growth factor receptor, c-Kit, and c-Met ( 5 , 6 ). The ALTER1202 study ( 7 , 8 ) showed that anlotinib could be a third-line standard treatment for patients with ES-SCLC for whom chemotherapy failed.…”
Section: Introductionmentioning
confidence: 99%